Decreasing plasma soluble IL-1 receptor antagonist and increasing monocyte activation early post-transplant may be involved in pathogenesis of delayed graft function in renal transplant recipients - Sadeghi, Mahmoud; Daniel, Volker; Naujokat, Cord; Schmidt, Jan; Mehrabi, Arianeb; Zeier, Martin; Opelz, Gerhard (Clinical transplantation, 2010)
Sadeghi M, Daniel V, Naujokat C, Schmidt J, Mehrabi A, Zeier M, Opelz G. Decreasing plasma soluble IL-1 receptor antagonist and increasing monocyte activation early post-transplant may be involved in pathogenesis of delayed graft function in renal transplant recipients Clin Transplant 2010: 24: 415-423. © 2009 John Wiley & Sons A/S. Abstract: Delayed graft function (DGF) increases the risk of acute allograft rejection and may affect long-term graft survival. We compared pre-transplant, early post-transplant, and late post-transplant serum creatinine (Cr) and plasma levels of neopterin, cytokines, and cytokine receptors/antagonists in patients with DGF (n = 39), slow graft function (SGF) (n = 43), or immediate graft function (IGF) (n = 30). Three and eight days post-transplant, plasma neopterin (p < 0.001; p < 0.001), Soluble Interleukin-6 (IL-6) receptor (R) (p = 0.002; p = 0.001), and IL-10 (p = 0.003; p = 0.001) were higher in DGF than IGF patients. One month post-transplant, plasma neopterin (p < 0.001) and IL-10 (p < 0.001) were higher in DGF than IGF patients. Three days post-transplant, the results indicated reduced sIL-1 receptor antognist (RA) production in DGF patients (p = 0.001). Simultaneously, plasma sIL-6R and IL-10 increased in DGF (p < 0.001; p = 0.003) and SGF (p = 0.007; p = 0.030) patients, indicating increased production of sIL-6R and IL-10. Lower sIL-1 production in DGF than IGF patients early post-transplant might promote the increased production of monocyte-derived neopterin, sIL-6R, and IL-10. This monocyte/macrophage activation might induce inflammation in the graft and subsequently cause an impairment of graft function. Blocking of monocyte activity after renal transplantation may be considered a potential approach for improving graft outcome.
Gesehen am 29.06.2023